Climatic and volcanic forcing of tropical belt northern boundary over the past 800 years. Issue 12 (December 2018) - Alfaro-Sánchez, R.; Nguyen, H.; Klesse, S.; Hudson, A.; Belmecheri, S.; Köse, N.; Diaz, H.; Monson, R.; Villalba, R.; Trouet, V.
Abstract The position of the northern boundary of the tropical belt affects the hydroclimate of many arid and semi-arid regions in the Northern Hemisphere. Widening of the tropical belt since the 1970s has largely been attributed to anthropogenic forcing. However, the relative influence of natural drivers of tropical belt expansion and contraction before this time is poorly understood. Here we use data on tree-ring widths from five mid-latitude regions in the Northern Hemisphere to reconstruct the movement of the northern boundary of the early spring tropical belt over the past 800 years (ad 1203–2003). Our reconstruction explains 45% of the interannual variance in the latitudinal extent of the Hadley circulation, a metric of the position of the tropical belt boundary. We find that the tropical belt contracted (expanded) during positive (negative) phases of the El Niño Southern Oscillation and Pacific North American teleconnection patterns. The tropical belt also contracted significantly following major volcanic events that injected sulfur into the stratosphere. The longest period of persistent tropical belt expansion occurred in the late sixteenth century, during one of the coldest periods of the Little Ice Age. Our results warn of potential socio-economic consequences of future variations in tropical belt width driven by natural climate variability or stratospheric aerosol injections, whether volcanic or artificial. Climate variability and volcanic forcing both influenced the latitudinal migration of the tropical belt over the past 800 years, according to an analysis of tree-ring widths in the Northern Hemisphere.